Glass paste for sealing electric vacuum device and preparation method thereof
By using glycosyl nonionic surfactant and modified nanoboronitride in glass slurry, the problem of insufficient sealing and thermal shock resistance in electrical vacuum device sealing is solved, and efficient and environmentally friendly glass slurry preparation is achieved, which is suitable for the sealing applications of electrical vacuum devices.
Patent Information
- Application Number
- CN202411830522.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-04
AI Technical Summary
It is difficult to develop a glass slurry for electrical vacuum device sealing, which can not only reduce environmental and human body hazards, but also have good sealing and thermal shock resistance.
The dispersion and fluidity of the glass slurry are improved by reducing the surface tension between the interface between the organic carrier and the solid powder, and the dispersion and compatibility of the nanoboronitride are improved by modifying the dispersion and compatibility of the nanoboronitride.
The high sealing, good wetting and thermal shock resistance of the glass slurry are achieved, the risk of pollution is reduced, and the process efficiency and quality are excellent.
Smart Images

Figure BDA0005185440500000091 
Figure BDA0005185440500000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass paste, and in particular relates to a glass paste for sealing electric vacuum devices and a preparation method thereof. Background Art
[0002] With the rapid progress of vacuum electronics, microelectronics, laser and infrared technologies, equipment is becoming increasingly miniaturized and structural components are becoming increasingly sophisticated. At the same time, vacuum devices are sealed by vacuum brazing technology. The materials of various components of vacuum devices are usually quite different, making it difficult to ensure the consistency of parameters such as the expansion coefficient. This can easily lead to defects and damage in the sealing parts during the heating or cooling process, posing a great challenge to the airtightness of vacuum devices.
[0003] There are various types of sealing materials on the market, which can be divided into three categories based on chemical composition: organic materials, glass materials and metal materials. Sealing sub-components of different materials and structures into a high mechanical strength and low leakage rate whole according to the expected design has always been one of the key research directions of vacuum devices and other sealed working equipment. However, organic materials are prone to decomposition when subjected to high temperatures above 200°C for a long time, and the conductivity of metal materials limits their application in the field of microelectronics. Therefore, for sealing materials that can withstand high temperatures, glass materials have become the focus of research and application.
[0004] Chinese patent CN 115466057 B discloses a composite glass paste and a preparation method thereof. The glass paste comprises the following components in parts by weight: 40-160 parts of composite glass powder and 5-30 parts of an organic phase carrier. The composite glass powder consists of a low-melting point glass powder and a high-melting point glass powder. The glass paste of the present invention realizes the special requirements of sealing in a relatively low temperature environment and being used in a high temperature environment. However, the composite glass powder contains lead elements, which will pollute the environment during processing and use and endanger human health. Chinese patent CN 116730629 B discloses a low-melting-point glass powder for high-temperature and high-humidity photovoltaic glass paste and its preparation method and application. The photovoltaic glass paste contains the following raw materials: 31-39% titanium dioxide, 39-47% low-melting-point glass powder, 15-20% organic solvent and 2-5% other additives by weight percentage. The other additives are leveling agent BYK-333, defoaming agent BYK-1709 and dispersant DP-488 in a mass ratio of 2:2:1. This invention can solve the problem that photovoltaic glass paste is easy to fall off and crack in outdoor high temperature and high humidity environment. However, it lacks some active ingredients, so its sealing performance is general when used for sealing electric vacuum devices. Chinese patent CN 110790511 B discloses a low-temperature, environmentally friendly black glass slurry with high optical density. The glass slurry includes the following raw materials, calculated by weight percentage of 100%, including 40-75% broken glass blocks, 15-45% black pigment, and 12-25% varnish. The glass slurry prepared by this invention does not contain Pb and Cr elements, complies with the EU RoHS environmental protection standard, greatly improves the optical density of the glass slurry, and has good glaze gloss after tempering at high temperature, with extremely high blackness and excellent acid and alkali resistance. However, although this glass slurry has good high temperature resistance, it may break or be damaged when the temperature changes rapidly, and has poor thermal shock resistance.
[0005] Therefore, there is an urgent need to develop a glass paste for sealing electric vacuum devices, which can not only reduce environmental and human hazards, but also have good sealing and thermal shock resistance. Summary of the invention
[0006] In view of the existing technical problems, the purpose of the present invention is to provide a glass paste for sealing electric vacuum devices and a preparation method thereof. The glass paste of the present invention has good sealing performance, good efficiency and quality of the debinding process, low pollution, good wettability and thermal shock resistance, and has good market prospects.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] On the one hand, the present invention provides a glass paste for sealing electric vacuum devices. The glass paste comprises the following raw materials in parts by weight: 40-60 parts of glass powder and 20-40 parts of organic carrier; wherein each part of the organic carrier comprises the following raw materials: 50-80 parts of organic solvent, 8-15 parts of ethyl cellulose, 5-10 parts of dispersant, 2-6 parts of surfactant, 0.5-1.5 parts of thixotropic agent, 0.1-0.2 parts of defoaming agent and 0.1-0.2 parts of leveling agent.
[0009] The reaction mechanism and effects of the present invention are as follows:
[0010] 1. Since sugar-based surfactants have the characteristics of being degradable, low in pollution and biocompatible, the present invention uses dimethyl adipate and 1,3-propylenediamine to synthesize amine substances, and further grafts lactobionic acid to prepare a sugar-based nonionic surfactant containing an amide group, which effectively reduces the surface tension of the interface between the organic carrier and the solid powder. On the one hand, the addition of surfactants can significantly improve the dispersibility and fluidity of the glass slurry, improve the wettability of the substrate, and thus improve the sealing; on the other hand, the symmetrical structure of the surfactant helps to improve stability, which is conducive to better dispersion of solid particles when heating the glass slurry, and further improves the sealing and thermal shock resistance of the glass slurry.
[0011] 2. Boron nitride has excellent high temperature resistance and is chemically inert to most molten metals, glass and slag, which can further improve thermal shock resistance. However, boron nitride is prone to poor dispersibility. Conventional methods directly use coupling agents to modify boron nitride. After the modified boron nitride is directly added, the modified boron nitride does not participate in the polymer reaction, so it is easy to cause stratification and performance degradation after long-term storage.
[0012] The present invention uses 3-mercaptopropyltriethoxysilane as a silane coupling agent to modify castor oil, and then adds mercapto groups to the unsaturated double bonds of castor oil; then, the silane bond is used to couple with nano boron nitride to improve the surface of boron nitride. On the one hand, compared with directly adding nano boron nitride to the slurry, the modified boron nitride has better dispersibility and compatibility; at the same time, adding nano boron nitride to the glass slurry can use its elastic deformation characteristics to reduce the thermal stress generated at the interface due to the difference in thermal expansion coefficient, improve the thermal shock resistance, and then help improve the adhesion strength between the glass slurry and the underlying material. On the other hand, castor oil has the disadvantages of poor thermal stability and weather resistance due to the presence of unsaturated double bonds, and the modified castor oil, an intermediate product in the modification process, not only has good storage stability, but can also be used as a thixotropic agent to enable the glass slurry to obtain good thixotropy, thickening and anti-settling properties, which is beneficial to control the fluidity and leveling of the slurry. In addition, during the preparation of the glass slurry, heating may cause a certain degree of cross-linking between the modified nano-boron nitride and the thixotropic agent carboxymethyl cellulose, thereby increasing the cross-linking density and thereby improving the sealing of the glass slurry.
[0013] 3. The present invention can effectively improve the thermal stability and decomposition characteristics of the organic carrier by adjusting the ratio of each component in the organic carrier, thereby improving the debinding efficiency; at the same time, by optimizing the composition of the glass powder, the melting point and softening point of the glass powder can be changed, thereby improving the debinding process.
[0014] In some embodiments, each part of the glass powder contains the following raw materials, by weight: 15-25 parts of SiO2, 35-50 parts of B2O3, 10-22 parts of ZnO, and 10-18 parts of Na2O3.
[0015] In some embodiments, the method for preparing the surfactant comprises the following steps:
[0016] S1. Add dimethyl adipate and 1,3-propylenediamine to a reaction kettle, heat to 80-100° C., add potassium hydroxide, react for 40-60 hours, distill under reduced pressure, recrystallize, filter, and wash to obtain an intermediate product;
[0017] S2. The intermediate product obtained in step S1 and methanol are mixed, stirred, lactobionic acid is added, an inert gas is introduced, heated to 85-100° C., kept warm for 10-15 hours, cooled, and rotary evaporated to obtain a surfactant.
[0018] In some embodiments, the molar ratio of dimethyl adipate to 1,3-propylenediamine in step S1 is 1:(4-6).
[0019] In some embodiments, the molar ratio of the intermediate product to lactobionic acid in step S2 is 1:(1-1.25).
[0020] In some embodiments, the glass paste further comprises 5-10 parts by weight of modified nano boron nitride.
[0021] In some embodiments, the method for preparing the modified nano-boron nitride comprises the following steps:
[0022] A1. Mixing a silane coupling agent and castor oil, stirring, introducing an inert gas, adding a catalyst, heating the reaction, cooling, and obtaining an intermediate product;
[0023] A2. The intermediate product obtained in step A1 and nano-boron nitride are mixed, stirred, heated for reaction, cooled, and dried to obtain modified nano-boron nitride.
[0024] In some embodiments, the mass ratio of the silane coupling agent to castor oil in step A1 is 1:(6-17).
[0025] In some embodiments, the mass ratio of the catalyst to castor oil in step A1 is 1:(10-28).
[0026] Preferably, the silane coupling agent in step A1 is 3-mercaptopropyltriethoxysilane, model KH580; and the catalyst is azobisisobutyronitrile.
[0027] In some embodiments, the mass ratio of the intermediate product to nano-boron nitride in step A2 is 10:(1-2.8).
[0028] In some embodiments, the organic solvent is any one or more of terpineol, turpentine, butyl carbitol, butyl carbitol acetate, isopropyl alcohol, propylene glycol, ethyl oleate and diethylene glycol butyl ether.
[0029] In some embodiments, the dispersant is an acrylic copolymer.
[0030] In some embodiments, the thixotropic agent is any one or more of carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose.
[0031] Preferably, the thixotropic agent is carboxymethyl cellulose.
[0032] In some embodiments, the defoaming agent is a silicone defoaming agent.
[0033] In some embodiments, the leveling agent is a silicone leveling agent.
[0034] Another aspect of the present invention provides a method for preparing a glass paste for sealing an electric vacuum device, comprising the following steps:
[0035] 1. Grind and sieve the glass powder to obtain fine glass powder for later use; add ethyl cellulose, dispersant, surfactant, thixotropic agent, defoaming agent and leveling agent to the organic solvent in sequence, heat to 80-90°C, keep warm and stir for 0.5-1h to obtain an organic carrier for later use;
[0036] 2. Mix the fine glass powder and modified nano boron nitride obtained in step 1, grind them and add them to the organic carrier obtained in step 1, heat them to 80-90° C., keep them warm and stir for 1-2 hours to obtain glass slurry.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. The glass paste of the present invention has good sealing performance, high efficiency and quality of the binder removal process, low pollution, and good wettability and thermal shock resistance.
[0039] 2. The present invention prepares a sugar-based nonionic surfactant containing an amide group, which effectively reduces the surface tension at the interface between the organic carrier and the solid powder, allowing the organic carrier to fully wet the solid particles. At the same time, the symmetrical structure of the surfactant helps to improve thermal shock resistance.
[0040] 3. The modified nano boron nitride of the present invention has better dispersibility and compatibility. First, the modified boron nitride has good storage stability and good thermal shock resistance, which helps to improve the adhesion strength between the glass slurry and the underlying material; second, the modified castor oil, an intermediate product in the modification process, can also be used as a thixotropic agent to enable the glass slurry to obtain good thixotropy, thickening and anti-settling properties, improve the leveling properties of the glass slurry, and thereby enhance the sealing of the glass slurry. DETAILED DESCRIPTION
[0041] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, rather than to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0042] According to the ratios of the raw materials and the preparation methods specified in the following examples and comparative examples, various glass pastes were prepared.
[0043] In order to facilitate those skilled in the art to implement the present invention, some raw material manufacturers of the embodiments and comparative examples are described as follows:
[0044] Defoaming agent: purchased from Qingdao Zhongbao Silicon Material Technology Co., Ltd., model ZBH-301;
[0045] Dispersant: purchased from Guangzhou Si Tu Yuan Chemical Co., Ltd., model BYK-2020;
[0046] Leveling agent: purchased from Shanghai Zhenlishi Network Technology Co., Ltd., model WE 3220;
[0047] Carboxymethyl cellulose: purchased from Renqiu Shuangcheng Chemical Products Factory;
[0048] Ethyl cellulose: purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.;
[0049] Castor oil: purchased from Guangzhou Hehui Chemical Co., Ltd.;
[0050] Nano boron nitride: particle size is 100nm;
[0051] Other raw materials are not specially specified and can be purchased from the market.
[0052] Preparation Example 1
[0053] The preparation method of surfactant A comprises the following steps:
[0054] S1. 0.4 mol of dimethyl adipate and 2 mol of 1,3-propylenediamine were added to a reaction kettle, heated to 90°C, 0.2 mol of potassium hydroxide was added, reacted for 50 hours, distilled under reduced pressure, recrystallized with methanol, filtered, and washed with anhydrous ether three times to obtain an intermediate product;
[0055] S2. Add 0.25 mol of the intermediate product obtained in step S1 and 400 ml of methanol to a reaction vessel, stir for 1 hour, add 0.3 mol of lactobionic acid, introduce nitrogen, heat to 95°C, keep the reaction warm for 12 hours, cool to room temperature, and rotary evaporate to obtain surfactant A.
[0056] Preparation Example 2
[0057] The preparation method of surfactant B is the same as that of Preparation Example 1, except that the amount of 1,3-propylenediamine added in step S1 is 1.52 mol.
[0058] Preparation Example 3
[0059] The preparation method of surfactant C is the same as that of Preparation Example 1, except that the amount of lactobionic acid added in step S2 is 0.2 mol.
[0060] Preparation Example 4
[0061] The preparation method of modified nano boron nitride A comprises the following steps:
[0062] A1. 2 g of 3-mercaptopropyltriethoxysilane was mixed with 20 g of castor oil, stirred for 30 min, nitrogen was introduced, 1 g of azobisisobutyronitrile was added, heated to 75 ° C for 4 h, and cooled to room temperature to obtain an intermediate product;
[0063] A2. Mix 20 g of the intermediate product obtained in step A1 and 3.8 g of nano-boron nitride, stir for 30 min, heat to 75 ° C for 4 h, cool to room temperature, and dry at 90 ° C for 2 h to obtain modified nano-boron nitride A.
[0064] Preparation Example 5
[0065] The preparation method of modified nano-boron nitride B is the same as that of Preparation Example 1, except that the amount of castor oil added in step A1 is 36 g.
[0066] Preparation Example 6
[0067] The preparation method of modified nano-boron nitride C is the same as that of Preparation Example 1, except that the amount of nano-boron nitride added in step A2 is 1.6 g.
[0068] Example 1
[0069] A glass paste for sealing an electric vacuum device, comprising the following raw materials by weight: 50 parts of glass powder, 30 parts of an organic carrier, and 7.5 parts of modified nano boron nitride A; wherein:
[0070] Each portion of the organic vehicle contains the following raw materials: 65 portions of organic solvent, 11.5 portions of ethyl cellulose, 7.5 portions of dispersant, 4 portions of surfactant A, 1 portion of thixotropic agent, 0.15 portions of defoaming agent, and 0.15 portions of leveling agent; each portion of the glass powder contains the following raw materials: 20 portions of SiO2, 42.5 portions of B2O3, 16 portions of ZnO, and 14 portions of Na2O3;
[0071] The organic solvent is terpineol, isopropyl alcohol and diethylene glycol butyl ether, and the mass ratio of the three is 3:1:1.5;
[0072] The dispersant is acrylic copolymer BYK-2020, the thixotropic agent is carboxymethyl cellulose, the defoaming agent is silicone defoaming agent ZBH-301, and the leveling agent is silicone leveling agent WE 3220.
[0073] The method for preparing the glass paste of this embodiment comprises the following steps:
[0074] 1. Grind and sieve the glass powder after mixing to obtain fine glass powder with an average particle size of 0.8 microns, which is set aside; add ethyl cellulose, dispersant, surfactant A, thixotropic agent, defoaming agent and leveling agent to the organic solvent in sequence, heat to 85°C, keep warm and stir for 45 minutes to obtain an organic carrier, which is set aside;
[0075] 2. Mix the fine glass powder obtained in step 1 and modified nano boron nitride A, grind them and add them to the organic carrier obtained in step 1, heat them to 85° C., keep them warm and stir for 1.5 hours to obtain glass slurry.
[0076] Example 2
[0077] A glass paste for sealing an electric vacuum device, comprising the following raw materials by weight: 40 parts of glass powder, 20 parts of an organic carrier, and 5 parts of modified nano boron nitride A; wherein:
[0078] Each portion of the organic vehicle contains the following raw materials: 50 parts of organic solvent, 8 parts of ethyl cellulose, 5 parts of dispersant, 2 parts of surfactant A, 0.5 parts of thixotropic agent, 0.1 parts of defoaming agent, and 0.1 parts of leveling agent; each portion of the glass powder contains the following raw materials: 15 parts of SiO2, 35 parts of B2O3, 10 parts of ZnO, and 10 parts of Na2O3;
[0079] The organic solvent is terpineol, isopropyl alcohol and diethylene glycol butyl ether, and the mass ratio of the three is 3:1:1.5;
[0080] The dispersant is acrylic copolymer BYK-2020, the thixotropic agent is carboxymethyl cellulose, the defoaming agent is silicone defoaming agent ZBH-301, and the leveling agent is silicone leveling agent WE 3220.
[0081] The method for preparing the glass paste of this embodiment comprises the following steps:
[0082] 1. Grind and sieve the glass powder after mixing to obtain fine glass powder with an average particle size of 0.8 microns, which is set aside; add ethyl cellulose, dispersant, surfactant A, thixotropic agent, defoaming agent and leveling agent to the organic solvent in sequence, heat to 90°C, keep warm and stir for 30 minutes to obtain an organic carrier, which is set aside;
[0083] 2. Mix the fine glass powder obtained in step 1 and modified nano boron nitride A, grind them and add them to the organic carrier obtained in step 1, heat them to 90° C., keep them warm and stir for 1 hour to obtain glass slurry.
[0084] Example 3
[0085] A glass paste for sealing an electric vacuum device, comprising the following raw materials by weight: 60 parts of glass powder, 40 parts of an organic carrier, and 10 parts of modified nano boron nitride A; wherein:
[0086] Each portion of the organic vehicle contains the following raw materials: 80 parts of organic solvent, 15 parts of ethyl cellulose, 10 parts of dispersant, 6 parts of surfactant A, 1.5 parts of thixotropic agent, 0.2 parts of defoaming agent, and 0.2 parts of leveling agent; each portion of the glass powder contains the following raw materials: 25 parts of SiO2, 50 parts of B2O3, 22 parts of ZnO, and 18 parts of Na2O3;
[0087] The organic solvent is terpineol, isopropyl alcohol and diethylene glycol butyl ether, and the mass ratio of the three is 3:1:1.5;
[0088] The dispersant is acrylic copolymer BYK-2020, the thixotropic agent is carboxymethyl cellulose, the defoaming agent is silicone defoaming agent ZBH-301, and the leveling agent is silicone leveling agent WE 3220.
[0089] The method for preparing the glass paste of this embodiment comprises the following steps:
[0090] 1. Grind and sieve the glass powders after mixing to obtain fine glass powders with an average particle size of 0.8 microns, which are set aside; add ethyl cellulose, dispersant, surfactant A, thixotropic agent, defoaming agent and leveling agent to the organic solvent in sequence, heat to 80°C, and stir for 60 minutes to obtain an organic carrier, which is set aside;
[0091] 2. Mix the fine glass powder obtained in step 1 and modified nano boron nitride A, grind them and add them to the organic carrier obtained in step 1, heat them to 80° C., keep them warm and stir for 2 hours to obtain glass slurry.
[0092] Example 4
[0093] A glass paste for sealing an electric vacuum device, wherein the glass paste comprises the following raw materials by weight: 50 parts of glass powder and 30 parts of an organic carrier; wherein:
[0094] Each portion of the organic vehicle contains the following raw materials: 65 portions of organic solvent, 11.5 portions of ethyl cellulose, 7.5 portions of dispersant, 4 portions of surfactant A, 1 portion of thixotropic agent, 0.15 portions of defoaming agent, and 0.15 portions of leveling agent; each portion of the glass powder contains the following raw materials: 20 portions of SiO2, 42.5 portions of B2O3, 16 portions of ZnO, and 14 portions of Na2O3;
[0095] The organic solvent is terpineol, isopropyl alcohol and diethylene glycol butyl ether, and the mass ratio of the three is 3:1:1.5;
[0096] The dispersant is acrylic copolymer BYK-2020, the thixotropic agent is carboxymethyl cellulose, the defoaming agent is silicone defoaming agent ZBH-301, and the leveling agent is silicone leveling agent WE 3220.
[0097] The method for preparing the glass paste of this embodiment comprises the following steps:
[0098] 1. Grind and sieve the glass powder after mixing to obtain fine glass powder with an average particle size of 0.8 microns, which is set aside; add ethyl cellulose, dispersant, surfactant A, thixotropic agent, defoaming agent and leveling agent to the organic solvent in sequence, heat to 85°C, keep warm and stir for 45 minutes to obtain an organic carrier, which is set aside;
[0099] 2. Add the fine glass powder obtained in step 1 to the organic carrier obtained in step 1, heat to 85° C., and stir for 1.5 hours to obtain glass slurry.
[0100] Example 5
[0101] A glass paste for sealing electric vacuum devices and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified nano-boron nitride B is used to replace modified nano-boron nitride A.
[0102] Example 6
[0103] A glass paste for sealing an electric vacuum device and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified nano-boron nitride C is used to replace modified nano-boron nitride A.
[0104] Example 7
[0105] A glass paste for sealing an electric vacuum device and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of surfactant B is used to replace surfactant A.
[0106] Example 8
[0107] A glass paste for sealing an electric vacuum device and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of surfactant C is used to replace surfactant A.
[0108] Comparative Example 1
[0109] A glass paste for sealing electric vacuum devices and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of commercially available nano boron nitride with a particle size of 100 nm is used to replace the modified nano boron nitride A.
[0110] Comparative Example 2
[0111] A glass paste for sealing electric vacuum devices and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of Span 80 is used to replace surfactant A.
[0112] Effect evaluation:
[0113] The glass pastes prepared in the above-mentioned Examples 1-8 and Comparative Examples 1-2 were tested and analyzed, and the specific results are shown in Table 1.
[0114] Performance Test:
[0115] (1) Expansion coefficient test: The obtained glass slurry is printed on a microcrystalline glass (with a heating functional layer printed thereon), and the thickness after printing is 20-25 μm by wet grinding. After drying at 150° C. for 3-5 min, the microcrystalline glass substrate is covered thereon and sintered in a muffle furnace at 600° C. for 20 min to obtain a double-layer glass sample, and the expansion coefficient is tested.
[0116] (2) Thermal shock resistance test: Double-glazed glass samples are tested in the following order: placed at 450°C for 30 minutes, immediately placed in cold water, and cycled 25 times. The samples are then allowed to recover at normal temperature and humidity for 1 hour. After that, the samples are measured. The test results are considered acceptable if the bonding layer of the double-glazed glass does not crack, indicating good thermal shock resistance.
[0117] Table 1
[0118]
[0119]
[0120] From the results in Table 1, it can be seen that the expansion coefficient of the glass paste prepared in Examples 1-3 is appropriate, matching the expansion coefficient of the sealed material microcrystalline glass, and thus has good sealing and better thermal shock resistance; the expansion coefficient of the glass paste prepared in Example 4 is also appropriate, but because no modified nano-boron nitride is added, the expansion coefficient is slightly higher than that of Example 1, but it also meets the process requirements.
[0121] Examples 5-6 and Comparative Example 1 Compared with Example 1, when preparing modified nano-boron nitride, Example 5 changes the mass ratio of silane coupling agent to castor oil, making castor oil easily oxidized and affecting the overall performance of the slurry. Example 6 changes the mass ratio of the intermediate product to nano-boron nitride, making the dispersion stability of nano-boron nitride slightly poor, which will affect the expansion coefficient and thermal shock resistance of the slurry. Comparative Example 1 uses an equal amount of commercially available nano-boron nitride to replace modified nano-boron nitride A, which greatly reduces the dispersibility of nano-boron nitride, which will increase the expansion coefficient of the slurry and weaken the thermal shock resistance.
[0122] Compared with Example 1, in the preparation of surfactants, Example 7 changes the molar ratio of dimethyl adipate and 1,3-propylenediamine, resulting in loss of symmetrical structure and poor stability; Example 8 changes the molar ratio of the intermediate product and lactobionic acid, resulting in a slight decrease in wettability, which will affect the expansion coefficient and thermal shock resistance of the slurry; Comparative Example 2 uses an equal amount of Span 80 to replace surfactant A, and this surfactant cannot wet the solid particles well, which will increase the expansion coefficient of the slurry and weaken the thermal shock resistance.
[0123] The above is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present application. Although the present application is disclosed as above in the preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution.
Claims
1. A glass paste for sealing electric vacuum devices, characterized in that: In parts by weight, the glass slurry comprises the following raw materials: 40-60 parts of glass powder and 20-40 parts of organic carrier; wherein each part of the organic carrier comprises the following raw materials: 50-80 parts of organic solvent, 8-15 parts of ethyl cellulose, 5-10 parts of dispersant, 2-6 parts of surfactant, 0.5-1.5 parts of thixotropic agent, 0.1-0.2 parts of defoaming agent and 0.1-0.2 parts of leveling agent.
2. The glass paste for sealing electric vacuum devices according to claim 1, characterized in that: In parts by weight, each part of the glass powder contains the following raw materials: 15-25 parts of SiO2, 35-50 parts of B2O3, 10-22 parts of ZnO, and 10-18 parts of Na2O3.
3. The glass paste for sealing electric vacuum devices according to claim 1, characterized in that: The preparation method of the surfactant comprises the following steps: S1. Add dimethyl adipate and 1,3-propylenediamine to a reaction kettle, heat to 80-100° C., add potassium hydroxide, react for 40-60 hours, distill under reduced pressure, recrystallize, filter, and wash to obtain an intermediate product; S2. The intermediate product obtained in step S1 and methanol are mixed, stirred, lactobionic acid is added, an inert gas is introduced, heated to 85-100° C., kept warm for 10-15 hours, cooled, and rotary evaporated to obtain a surfactant.
4. The glass paste for sealing electric vacuum devices according to claim 3, characterized in that: The molar ratio of dimethyl adipate to 1,3-propylenediamine in step S1 is 1:(4-6).
5. The glass paste for sealing electric vacuum devices according to claim 3, characterized in that: The molar ratio of the intermediate product to lactobionic acid in step S2 is 1:(1-1.25).
6. The glass paste for sealing electric vacuum devices according to claim 1, characterized in that: In parts by weight, the glass paste also includes 5-10 parts of modified nano boron nitride.
7. The glass paste for sealing electric vacuum devices according to claim 6, characterized in that: The preparation method of the modified nano boron nitride comprises the following steps: A1. Mixing a silane coupling agent and castor oil, stirring, introducing an inert gas, adding a catalyst, heating the reaction, cooling, and obtaining an intermediate product; A2. The intermediate product obtained in step A1 and nano-boron nitride are mixed, stirred, heated for reaction, cooled, and dried to obtain modified nano-boron nitride.
8. The glass paste for sealing electric vacuum devices according to claim 7, characterized in that: The mass ratio of the silane coupling agent to castor oil in step A1 is 1:(6-17).
9. The glass paste for sealing electric vacuum devices according to claim 7, characterized in that: The mass ratio of the intermediate product to nano-boron nitride in step A2 is 10:(1-2.8).
10. A method for preparing a glass paste for sealing an electric vacuum device according to any one of claims 6 to 9, characterized in that: The following steps are included:
1. Grind and sieve the glass powder to obtain fine glass powder for later use; add ethyl cellulose, dispersant, surfactant, thixotropic agent, defoaming agent and leveling agent to the organic solvent in sequence, heat to 80-90°C, keep warm and stir for 0.5-1h to obtain an organic carrier for later use; 2. Mix the fine glass powder and modified nano boron nitride obtained in step 1, grind them and add them to the organic carrier obtained in step 1, heat them to 80-90° C., keep them warm and stir for 1-2 hours to obtain glass slurry.
Citation Information
Patent Citations
A low-temperature, environmentally friendly black glass paste with high optical density
CN110790511B
A composite glass paste and its preparation method
CN115466057B
A low melting point glass powder for high temperature and high humidity resistant photovoltaic glass paste and its preparation method and application
CN116730629B